2014
DOI: 10.1063/1.4897299
|View full text |Cite
|
Sign up to set email alerts
|

The field induced e31,f piezoelectric and Rayleigh response in barium strontium titanate thin films

Abstract: The electric field induced e 31,f piezoelectric response and tunability of Ba 0.7 Sr 0.3 TiO 3 (70:30) and Ba 0.6 Sr 0.4 TiO 3 (60:40) thin films on MgO and silicon was measured. The relative dielectric tunabilities for the 70:30 and 60:40 compositions on MgO were 83% and 70%, respectively, with a dielectric loss of less than 0.011 and 0.004 at 100 kHz. A linear increase in induced piezoelectricity to À3.0 C/m 2 and À1.5 C/m 2 at 110 kV/cm was observed in Ba 0.6 Sr 0.4 TiO 3 on MgO and Ba 0.7 Sr 0.3 TiO 3 on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…A similar idea was also proposed by Garten et al for BST thin films and ceramics. 10,12,17,50 They demonstrated that a strain gradient may polarize BST samples and suggested that it happens by the reorientation of residual ferroelectric domains (or another kind of polar entities) whose dynamics can be described by Eq. (1).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…A similar idea was also proposed by Garten et al for BST thin films and ceramics. 10,12,17,50 They demonstrated that a strain gradient may polarize BST samples and suggested that it happens by the reorientation of residual ferroelectric domains (or another kind of polar entities) whose dynamics can be described by Eq. (1).…”
mentioning
confidence: 99%
“…22,23 The experimental values of the flexoelectric coefficients in this solid solution cannot be reconciled easily with theoretical predictions. [24][25][26][27] Garten et al 10,12,17,28 proposed that in their BST thin films and ceramics, the flexoelectric polarization in the paraelectric phase is enhanced by polarization from residual ferroelectric domains (or microdomains or micropolar regions), leading to exceptionally large apparent flexoelectric coefficients. A similar result was reported by Narvaez and Catalan for the flexoelectric response in the paraelectric phase of a single crystal relaxor-ferroelectric.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, current research efforts have focused on increasing film quality as a means to improve the tunable figure of merit (FOM) . However, other routes exist to further improve FOM values in BST, such as reducing the residual ferroelectric and piezoelectric loss contributions, which are less widely addressed …”
Section: Introductionmentioning
confidence: 99%